Tinjauan Skizofrenia Secara Psikoneuroimunologi - Muthmainnah Muthmainnah; Fazil Amris (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Schizophrenia is a psychiatric diagnosis that indicates a mental disorder characterized by abnormal perception or disturbances regarding reality. A number of abnormalities in patients with schizophrenia have been linked to the field of psychoneuroimmunology. Schizophrenia occurs due to various factors (multifactorial), including genetic factors, environment and neurological abnormalities. Psychologically, schizophrenia occurs due to a mismatch between affection, cognition and behavior. Neurologically, in schizophrenia there is overactivity of the dopaminergic system, in the main dopamine pathway, namely in the mesolimbic, mesocortex, nigrostriatal and tuberoinfundibular, as well as increased serotonergic activity. Meanwhile, immunologically, schizophrenia occurs due to changes in microglia activity which affects the immune response and an increase in pro-inflammatory cytokines. The clinical manifestations of schizophrenia consist of 3 categories of symptoms, in the form of positive symptoms, negative symptoms and cognitive symptoms/interpersonal relationship disorders. Management of schizophrenia is carried out comprehensively with pharmacological antipsychotic treatment and psychosocial therapy which aims to improve quality of life and reduce morbidity and mortality of the disease.